(3GdhLjR aj TQGM COGA GdbQGA GdKeGfjI CFeI GdCeUGQ GdNeSIs - (3GdMSf Hf Ydj Hf EHQGgje Hf jROGO GdCghGRj, CHh Ydj,J (B446 (3g` s
(3ChdgG (B:s
(3CNHQfi GdTjN Gdabjg GHf THQ GdgeOGfi bQGAI efi Ydjg ai eOjfI RHjO CeG HYO MeO Gddg GdQMje EHJOi HPcQ eG ENJda ajg GdbQGA GdKeGfjI GdeTghQhf s
(3BNQgG (B:s
(3hhba bfHd HGdJcHjQ Ydi eLGgO hQaYg GdHRi Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3Ydi gGeTgG HYV GdJYdjbGJs
(3hai BNQgG ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs